Enhanced germination of seeds native to Brazil: A comparative analysis between free and nanoencapsulated gibberellic acid in Dyckia sp. (Bromeliaceae) - de Paula, Jean Carlo Baudraz; Guariz, Hugo Roldi; de Moraes, Kauê Alexandre Monteiro; Shimizu, Gabriel Danilo; de Faria, Ricardo Tadeu; de Oliveira, Halley Caixeta; Fraceto, Leonardo Fernandes [UNESP]; Pereira, Anderson Espirito Santo [UNESP] (De Gruyter, 2023)
Brazil is home to a great diversity of species of the genus Dyckia. However, many of these species are threatened due to habitat destruction and predatory exploitation. An alternative to conserving these plants is sexual propagation using plant regulators to stimulate germination. Gibberellic acid (GA3) is an effective regulator in this process, but its instability and ease of degradation pose challenges. Therefore, nanoencapsulation of GA3 could be used to protect the molecule and allow controlled release. In this study, the effects of different doses of GA3 were evaluated on the germination of four species: D. cabrerae, D. dusenii, D. pottiorum and D. walteriana. The first stage consisted of soaking the seeds in different concentrations of GA3, in which the species D. dusenii and D. walteriana showed significant responses to GA3, with an increase from 35% to more than 60% germination. However, the species D. cabrerae and D. pottiorum responded positively to GA3 only in vegetative growth parameters. In the second stage, the use of nanoparticles of alginate/chitosan (NP ALG/CS) and chitosan/tripolyphosphate (NP CS/TPP) containing GA3 was compared with free GA3 and with NPs without GA3. It was verified that the use of nanoencapsulated GA3 resulted in a more efficient germination response in D. walteriana seeds, using smaller doses of the regulator (between 0.75 mg ∙ L–1 and 1.0 mg ∙ L–1), mainly with the ALG/CS NPs. Therefore, the use of GA3 is recommended for D. dusenii and D. walteriana, and for the latter, nanoparticles containing ALG/CS-GA3 allow a reduction in the required dose.
Keywords: bromeliads; domestication; gibberellins; nanotechnology; plant growth regulators